1982
DOI: 10.1111/j.1467-1770.1982.tb00971.x
|View full text |Cite
|
Sign up to set email alerts
|

THE COMPREHENSIBILITY OF THREE VARIETIES OF ENGLISH FOR COLLEGE STUDENTS IN SEVEN COUNTRIES1

Abstract: Nonnative English speakers are almost always tested on their comprehension ability by listening to native speakers and answering questions based on what they have heard. Their comprehension of other nonnative speakers is seldom if ever tested. Nonnative speakers, however, do not limit their use of English to native speakers alone. Indeed they are increasingly using English with other nonnative speakers as well. The functional use of the term comprehensibility must therefore be broadened to include the evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 1 publication
4
80
1
3
Order By: Relevance
“…As reported in Munro et al (2006), Flege (1998) Sometimes speech perceived as heavily accented is also perceived as completely comprehensible and intelligible (Brodkey, 1972;Derwing & Munro, 1997;Munro & Derwing, 1995;Smith & Bisazza, 1982;Smith & Rafiqzad, 1979), thus, "listeners often assign good comprehensibility ratings to speech samples that they have also rated as heavily accented" (Derwing & Munro, 2005, p. 386). Results only show that listeners from different L1 backgrounds can equally recognize that accents are there.…”
Section: Accent Familiarity and Ratingmentioning
confidence: 98%
“…As reported in Munro et al (2006), Flege (1998) Sometimes speech perceived as heavily accented is also perceived as completely comprehensible and intelligible (Brodkey, 1972;Derwing & Munro, 1997;Munro & Derwing, 1995;Smith & Bisazza, 1982;Smith & Rafiqzad, 1979), thus, "listeners often assign good comprehensibility ratings to speech samples that they have also rated as heavily accented" (Derwing & Munro, 2005, p. 386). Results only show that listeners from different L1 backgrounds can equally recognize that accents are there.…”
Section: Accent Familiarity and Ratingmentioning
confidence: 98%
“…Some research has shown that familiarity with the speaker's accent facilitates comprehension and may thus lead to more lenient evaluations of the overall speech quality (Brodkey, 1972;Smith & Bisazza, 1982;Smith & Rafiqzad, 1979), whereas other studies have revealed lower tolerance of their peers' speech by nonnative speakers of the target second language (L2) than native speakers (Fayer & Krasinski, 1987;Sheorey, 1985). These conflicting findings may be partially due to differences in whether naive or trained raters are used, how adequately the raters are trained, and whether the raters undergo rigorous certification requirements.…”
Section: Executive Summarymentioning
confidence: 99%
“…Previous research on the assessment of second or foreign language learners' speaking proficiency by evaluators with different backgrounds has looked at untrained native versus nonnative evaluators (Brodkey, 1972;Caban, 2003;Fayer & Krasinski, 1987;Gorosch, 1973;Kim, 2009;Sheorey, 1985;Smith & Bisazza, 1982;Smith & Rafiqzad, 1979), trained native versus nonnative raters (Brown, 1995), laypeople versus professionals with training in a second or foreign language (Barnwell, 1989;Caban, 2003;Chalhoub-Deville, 1995;Galloway,1980;Gorosch, 1973;Hadden, 1991), male versus female raters (Eckes, 2005), raters with linguistic versus occupational backgrounds (Brown, 1995) However, in explorations of trained rater perceptions in an assessment context, the paramount goal is to reduce potential listener or rater bias and ensure fairness through rater training. In this section, we only review studies that use fairly clear scoring rubrics and raters with training in a second or foreign language or trained raters, which are typically required in an assessment or classroom evaluation context.…”
Section: Impact Of Rater Background Characteristics On the Scoring Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…As a prime instance, in Abeywickrama's study (2013) test takers from three different countries performed similarly even when the speakers shared the same native languages as the test takers, and students preferred native variety of English as the input in listening tests. Also, Smith and Bisazza (1982) found that Native American and British are more intelligible than native Chinese speakers. In another study, Stibbard and Lee (2006) aimed at finding the potential of using non-native English in listening tests.…”
Section: Discussionmentioning
confidence: 99%